Simulating a Multiproduct Barter Exchange Economy - Daniel Levy; Mark Bergen (Economic Inquiry, 1993)
We describe a multiproduct barter trading experiment in which students exchange real goods in an open market based on their own personal preference. The experiment is designed for simulating a pure exchange market in order to demonstrate the role of money and its functions in real economies by showing the limitations and inefficiencies of the traditional barter economy. In addition, the simulation is very effective in highlighting some of the key features that an object that serves as money needs to possess in order to function as an efficient medium of exchange, unit of account, and store of value.
Keywords: A22; E40; 330; Money; Demand for Money; Barter Exchange; Monetary Experiment; Functions of Money; Medium of Exchange; Store of Value; Unit of Account; Features of Money; Information Cost; Identification Cost